Phantom Tumors in COVID-19: A Case Report - Felita Ferdiana; Wayan Wahyu Semara Putra; Velensia Lawrence; Jennifer Mochtar (Jurnal Respirasi, 2022)
Introduction: A phantom tumor, or vanishing lung pseudotumor, is an atypical type of pleural effusion in which fluid is accumulated in the pleural cavity. It is a transient and well-demarcated pleural fluid accumulation in the interlobar pulmonary fissures. In this study, we reported a rare case of a pleural effusion appearing as a phantom tumor in COVID-19 without congestive heart failure. Case: A 29-year-old man was presented with complaints of dry cough, sore throat, fever, and fatigue. He denied shortness of breath and loss of taste and smell. He had no smoking habit and did not have any past medical history. Physical examinations were within normal limits, except for a slight fever. The laboratory examination showed positive SARS-CoV-2 RT-PCR and an increased liver function test. His chest X-ray revealed findings suggestive of a phantom tumor accompanied by bilateral pneumonia. The patient received COVID-19 treatments. A follow-up chest X-ray revealed the complete resolution of the lesion. Conclusion: A phantom tumor is a rare case. It is caused by heart disease and other causes, one of which is COVID-19. The treatment for this condition is based on the underlying disease.